1999
DOI: 10.1128/iai.67.5.2096-2102.1999
|View full text |Cite
|
Sign up to set email alerts
|

Down Regulation ofEntamoeba histolyticaVirulence by Monoxenic Cultivation withEscherichia coliO55 Is Related to a Decrease in Expression of the Light (35-Kilodalton) Subunit of the Gal/GalNAc Lectin

Abstract: Entamoeba histolytica virulence is related to a number of amebic components (lectins, cysteine proteinases, and amebapore) and host factors, such as intestinal bacterial flora. Trophozoites are selective in their interactions with bacteria, and the parasite recognition of glycoconjugates plays an important role in amebic virulence. Long-term monoxenic cultivation of pathogenic E. histolyticatrophozoites, strains HK-9 or HM-1:IMSS, with Escherichia coli serotype O55, which binds strongly to the Gal/GalNAc amebi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 42 publications
(58 reference statements)
2
28
0
Order By: Relevance
“…Virulence reduction following monoaxenic culture or culture in artificial media has been observed for Paramoeba invadens and E. histolytica . Virulence was restored for these species after passage through the target host (Jellett & Scheibling 1988; Padilla‐Vaca, Ankri, Bracha, Koole & Mirelman 1999). It is possible that involvement of a cryptic pathogen (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Virulence reduction following monoaxenic culture or culture in artificial media has been observed for Paramoeba invadens and E. histolytica . Virulence was restored for these species after passage through the target host (Jellett & Scheibling 1988; Padilla‐Vaca, Ankri, Bracha, Koole & Mirelman 1999). It is possible that involvement of a cryptic pathogen (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the glycoconjugate is galactose or N ‐acetylgalactosamine (Findlay 2001). As Padilla‐Vaca, Ankri, Bracha, Koole & Mirelman (1999) have shown that the glycoconjugate profile of the bacteria used as the nutritional lawn for cultured Entamoeba histolytica is crucial in deciding if the organism is to be pathogenic or not, similar studies are warranted for N. pemaquidensis. This mechanism may also be involved in the apparent preference of N. pemaquidensis for hyperplastic gill epithelium (Munday et al .…”
Section: Pathogenesismentioning
confidence: 99%
“…9,10 Old papers reported that gut bacteria, such as O55 Escherichia coli and Shigella dysenteriae, directly affect on the virulence of E. histolytica in vitro experiments. [11][12][13] Also, it was known that disease severity of autoimmune diseases, such as inflammatory bowel diseases and rheumatoid, are highly influenced by the gut microbiome.- [14][15][16] However, effect of gut microbiome on host immune response to external pathogen are rarely investigated in previous studies.…”
Section: Severity Of Entamoeba Histolytica Infection and The Gut Micrmentioning
confidence: 99%